2022
DOI: 10.3390/buildings12050590
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations on the Flexural Responses of Rubberised Concrete

Abstract: The increase in world population has led to a significant increase in the numbers of cars and used tyres. These tyres must be disposed of on an ongoing basis as a result of their consumption or deterioration. This can result in negative effects on the environment that must be preserved, especially from those materials, i.e., these waste materials are difficult to dispose of without special treatments. Hence, extensive experimental investigations and numerical simulations need to be conducted to use and recycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Due to the growing problem with waste tires worldwide, researchers are now focused on preparing rubberized concrete a widely used, greener construction material [2,3,7]. They combine with various binders shredded used tires as aggregate in varying degrees of filling and grinding, depending on the desired properties and designation [8]. Tire-derived aggregates (TDA) have been gaining more and more popularity in recent years [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the growing problem with waste tires worldwide, researchers are now focused on preparing rubberized concrete a widely used, greener construction material [2,3,7]. They combine with various binders shredded used tires as aggregate in varying degrees of filling and grinding, depending on the desired properties and designation [8]. Tire-derived aggregates (TDA) have been gaining more and more popularity in recent years [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies give different results. First research on rubberized concrete in the 1990s [8] found that the addition of rubber to a concrete mixture decreased the material's flexural and compressive strengths. It was also shown that cracking in concrete occurred more frequently than in conventional concrete due to the poor adhesion between rubber materials and other components of the concrete [2].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to experimental endeavors, numerical simulations have also offered valuable insights into the behavior of RRC [20][21][22][23]. This approach provides a granular view of the interactions between aggregates, rubber particles, and the cementitious matrix [24][25][26]. Traditional commercial finite element software, while powerful, is sometimes marred by challenges such as computational inefficiency and mesh sensitivity, especially when modeling complex materials like RRC [18,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%